Management of Residual Urban Spaces to Mitigate Environmental Pollution in A Peruvian Population Center - Vargas, Juana Victoria Bustinza; Ugarte, Soledad Jackeline Zegarra; Jimenez, Fatima Tiznado; Sapacayo, Lourdes Lacuta; Humpiri, Maria del Rosario Quispe; Mamani, Yudy Carol Bonifacio; Mamani, Ruth Analy Vargas (Journal of Posthumanism, 2025)
This research titled “Management of Residual Urban Spaces to Mitigate Environmental Pollution in the Alto Puno Population Center – 2024” aimed to determine how the management of residual urban spaces contributes to the mitigation of environmental pollution. This was a basic-theoretical study with an explanatory-causal level, using a quantitative approach, non-experimental cross-sectional design, and a hypothetico-deductive method. A probabilistic simple random sampling method was used to select 1,204 residents of the population center. The primary data collection technique was a survey using Likert-scale questionnaires. Key findings revealed a statistically significant influence of the management of residual urban spaces on the reduction of environmental pollution, as confirmed by the chi-square analysis (χ² = 47.558, p = 0.000 < 0.05). The study concludes that effective management of residual urban spaces significantly contributes to reducing environmental pollution, highlighting the relevance of their strategic planning within sustainable environmental frameworks.